2022
DOI: 10.1111/tbed.14633
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of hepatitis E virus from wild boar in China

Abstract: Hepatitis E virus (HEV), the causative agent of hepatitis E (HE), is classified into four major genotypes (1–4), with wild boar being the main natural reservoir for genotypes 3 and 4. However, little is known about the prevalence of HEV infection in wild boars in China. In this study, RT‐nested PCR and RT‐quantitative PCR were used to detect the HEV RNA in tissue samples taken from 331 free‐ranging wild boars collected between 2018 and 2020 from 24 regions across China, and the partial ORF2 genes or complete g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…A previous study [ 30 ] reported 2.7% (9/331) HEV RNA positivity from liver samples of wild boars in 25 provinces of China and 8.3% (1/12) in Xinjiang, consistent with our results (7.9%, 7/89). In our study, the HEV RNA positivity rate from liver samples was more than 10-fold higher than that in fecal samples ( Table S1 ), probably due to its hepatotropic characteristics that HEV RNA concentration in liver and bile were 10-fold higher than that in fecal and other samples [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A previous study [ 30 ] reported 2.7% (9/331) HEV RNA positivity from liver samples of wild boars in 25 provinces of China and 8.3% (1/12) in Xinjiang, consistent with our results (7.9%, 7/89). In our study, the HEV RNA positivity rate from liver samples was more than 10-fold higher than that in fecal samples ( Table S1 ), probably due to its hepatotropic characteristics that HEV RNA concentration in liver and bile were 10-fold higher than that in fecal and other samples [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…Wild boars can be infected with genotypes HEV-3–HEV-6 in other countries [ 45 ], and our study first identified sub-genotype HEV-4a from wild boars in China. Together with Gong et al [ 30 ], our results indicated that only HEV-4 (e.g., HEV-4a, HEV-4d, HEV-4g, and HEV-4h) circulated among wild boars in China. The high seroprevalence suggested that feral and farmed wild boars are zoonotic HEV reservoirs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to domestic pigs, PCVs have also been found to be prevalent in free-ranging wild boars in many foreign countries, including Italy ( Amoroso et al., 2021 ; Dei Giudici et al., 2020 ), Korea ( Song et al., 2020 ), Brazil ( Souza et al., 2021 ), Austria ( Auer et al., 2022 ), Ukraine ( Rudova et al., 2022 ), Hungary ( Cságola et al., 2006 ), Portugal ( de Sousa Moreira et al., 2022 ) and Germany ( Prinz et al., 2019 ), while the epizootiology of PCVs in Chinese free-ranging wild boars remains little research because of the difficulty of sample collection, although PCV2 infection was observed in hybrid wild boars from north-east China and PCVs in wild boar from Jiangxi Province of China ( Guo et al., 2019 ; Wu et al., 2022 ). Since wild boars are considered an important reservoir of animal and zoonotic pathogens, it is important to identify the epizootiology trends of important and emerging infectious diseases in wild boars for both livestock production and public health issues ( Meng et al., 2009 ; Li et al., 2019 ; Gong et al., 2022 ). In this study, the genetic characteristics and serological prevalence of PCVs in Chinese free-ranging wild boars were investigated.…”
Section: Introductionmentioning
confidence: 99%